Effects of social media use on desire for cosmetic surgery among young women - Walker, Candice E.; Krumhuber, Eva G.; Dayan, Steven; Furnham, Adrian (Current psychology (New Brunswick, N.J.), 2021)
A large body of research has documented the influence of traditional media formats (e.g. television programs, adverts) on young women’s consideration of cosmetic surgery. However, less is known about how newer forms of media such as social networking sites impact desire for cosmetic surgery. The present study aimed to examine whether exposure to images depicting facial cosmetic enhancements increases the desire for cosmetic surgery among young women. One-hundred and eighteen women, aged 18–29 years, indicated their social media use. This was followed by a task in which they viewed either images of facial cosmetic enhancements ( N = 59) or images of travel ( N = 59). Participants then indicated their satisfaction with their appearance, their mood and desire to undergo cosmetic enhancement. The results showed that viewing images of females who have undergone cosmetic enhancements affected young women’s desire for cosmetic surgery, especially if they spent a significant amount of time on social media, followed many accounts, and were less satisfied with their appearance. These findings have implications for parents, clinicians, and policy makers for understanding how internet habits, particularly the use of social media, influence the desire for cosmetic surgery, including the psychosocial motivations underlying those intentions.